Congenital heart disease presentations in the 15q11.2 microdeletion syndrome - Fifirig, Claudia-Ioana; Abraham, Sabu; Keavney, Bernard; Hentges, Kathryn E. (Frontiers in Genetics, 2025)
Congenital heart disease (CHD) is the most common type of birth defect and results from anomalies in the cardiogenesis process. There are multiple genetic mechanisms contributing to CHD, including copy number variants (CNVs). One such CNV is the 15q11.2 (BP1-BP2) microdeletion, which contains four evolutionarily conserved genes: NIPA1, NIPA2, CYFIP1, and TUBGCP5. The deletion causes a syndrome which includes developmental delays and multiple anatomical malformations including CHD. The link between the 15q11.2 (BP1-BP2) microdeletion and CHD has been previously described in the literature but not explored in terms of mechanistic investigations. The characteristics of the BP1-BP2 deletion also prove challenging in the context of genetic counselling. Here we discuss the 15q11.2 (BP1-BP2) microdeletion syndrome with a focus on CHD.